Burnin' down the house : home in African American literature - Prince, Valerie Sweeney (New York : Columbia University Press, 2005)
-- Cheryl A. Wall, Rutgers University.
Machine generated contents note: Introduction : a house is not a home -- 1. Living (just enough) for the city : Native son -- 2. Keep on moving don't stop : Invisible man -- 3. Get in the kitchen and rattle them pots and pans : The bluest eye -- 4. She's a brick house : Corregidora.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: American fiction -- African American authors -- History and criticism; Domestic fiction, American -- History and criticism; African American families in literature; African Americans -- Intellectual life; African American women in literature; African Americans in literature; Dwellings in literature; Families in literature; Home in literature; Roman américain -- Auteurs noirs américains -- Histoire et critique; Familles noires américaines dans la littérature.; Noirs américains -- Vie intellectuelle; Noirs américains dans la littérature.; Habitations dans la littérature.; Familles dans la littérature.; Foyer dans la littérature.; LITERARY CRITICISM -- American -- General; LITERARY CRITICISM -- American -- African American; African American families in literature; African American women in literature; African Americans in literature; African Americans -- Intellectual life; American fiction -- African American authors; Domestic fiction, American; Dwellings in literature; Families in literature; Home in literature; Criticism, interpretation, etc